PROBLEMATIKA GURU DALAM PROGRAM PEMBIASAAN KARAKTER SOPAN SANTUN SISWA SEKOLAH DASAR - Putri, Riyan Aryuning; Pratiwi, Ika Ari; Kuryanto, M. Syafruddin (P2M STKIP Siliwangi, 2022)
The purpose of this study was to describe the teacher's problems in the character habituation program for the students of SD 5 Jekulo Kudus. The method used is qualitative, the data collection in this research is direct observation, interviews, and documentation according to research needs, this research took place at SD 5 Jekulo, Kudus Regency, the subjects in this study were teachers and students at SD 5 Jekulo. The results showed that SD 5 Jekulo had a regular system of habituation of polite character, starting from the morning when the students went to school until the afternoon when the students came home from school. Internalization of teacher problems in the character habituation program for elementary school students 5 Jekulo Kudus can be classified; (1) problems in the role of students' behavior that does not respect elders; (2) problems in students doing mischief; and (3) teacher problems in patience. The solution that can be given is to provide understanding to students so that they do not have disrespectful feelings towards elders and the teacher sets a good example for students, directs students to always be polite to anyone, and teachers should always pay attention to the background of students in behaving and doing actions, and teachers should always be role models for students and be able to protect themselves from bad traits.